RocA Binds CsrS To Modulate CsrRS-Mediated Gene Regulation in Group A Streptococcus - Nicola N. Lynskey (American Society for Microbiology, 2019)
ABSTRACT The orphan regulator RocA plays a critical role in the colonization and pathogenesis of the obligate human pathogen group A Streptococcus. Despite multiple lines of evidence supporting a role for RocA as an auxiliary regulator of the control of virulence two-component regulatory system CsrRS (or CovRS), the mechanism of action of RocA remains unknown. Using a combination of in vitro and in vivo techniques, we now find that RocA interacts with CsrS in the streptococcal membrane via its N-terminal region, which contains seven transmembrane domains. This interaction is essential for RocA-mediated regulation of CsrRS function. Furthermore, we demonstrate that RocA forms homodimers via its cytoplasmic domain. The serotype-specific RocA truncation in M3 isolates alters this homotypic interaction, resulting in protein aggregation and impairment of RocA-mediated regulation. Taken together, our findings provide insight into the molecular requirements for functional interaction of RocA with CsrS to modulate CsrRS-mediated gene regulation. IMPORTANCE Bacterial two-component regulatory systems, comprising a membrane-bound sensor kinase and cytosolic response regulator, are critical in coordinating the bacterial response to changing environmental conditions. More recently, auxiliary regulators which act to modulate the activity of two-component systems, allowing integration of multiple signals and fine-tuning of bacterial responses, have been identified. RocA is a regulatory protein encoded by all serotypes of the important human pathogen group A Streptococcus. Although RocA is known to exert its regulatory activity via the streptococcal two-component regulatory system CsrRS, the mechanism by which it functions was unknown. Based on new experimental evidence, we propose a model whereby RocA interacts with CsrS in the streptococcal cell membrane to enhance CsrS autokinase activity and subsequent phosphotransfer to the response regulator CsrR, which mediates transcriptional repression of target genes.